Hip to be square : disruption in the U.S. mobile payment market - Markovich, Sarit, (SAGE knowledge. Cases., 2016)
Founded in San Francisco in 2009, Square finished 2012 as the darling of Silicon Valley; flush with more than $340 million in funding, the firm had grown to several hundred employees in just three short years. It processed more than $10 billion annually in credit and debit card payments from small business owners that used Square's smartphone-enabled card swipe device wherever cellular or wireless Internet services were available. However, Square's success had attracted new entrants into the mobile payments processing space, both in the United States and abroad, threatening to derail the company's remarkable trajectory. With its latest financing round valuing the company in excess of $3.4 billion, management and investors were considering which strategies would continue, even accelerate, the company's growth.